Desarrollo de un producto panificado bajo en calorías incorporando calabaza (Cucúrbita moschata Duchesne) y frutos secos - Muñoz Noboa, Pedro Naín (2025)
This curricular integration project aims to develop a low-calorie baked product that incorporates two products such as pumpkin and nuts. In order to achieve a healthy product, a sensory quality analysis of the developed baked product will be carried out, as well as determining the physical-chemical properties, this in accordance with the NTE INEN 2945: 2016-10 standard, and finally a microbiological evaluation of the finished product will be carried out. The following treatment 6: Pumpkin Cucúrbita Moschata Duchesne (75g) + Dried fruits (25g) + Stevia (1,25g) was obtained to this treatment a greater acceptance in sensory tests, other data were from those established by quality standards according to NTE INEN 2945, these were determined that there was no significant difference in the addition of pumpkin puree and dried fruits, thus giving a quality product, in case the molds and yeast do not exceed the limit as established by NOM 247 SSAI 2008 (25 to 250UFC). The results obtained from developing this product have been very favorable, so we have managed to test our knowledge acquired in the Agroindustry degree, and we have managed to obtain acceptance and construction criteria on the development of the low-calorie baked product with ingredients such as pumpkin Cucúrbita Moschata Duchesne and nuts, allowing us to obtain an adequate formulation, standardizing the process with expected results of optimal quality.